2013
DOI: 10.4028/www.scientific.net/amr.853.500
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Core Method of Lean Construction Management Mode and its Implementation

Abstract: Lean construction is an improvement on the traditional mode of construction of the project, to its use in the construction industry and project management in the study on lean thought construction management mode and implementation method based on lean thinking; origin, proposed the application of lean management in the construction industry on the basis of theory of lean production, through the analysis of the core of lean lean method based on construction management mode, the implementation of lean thinking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…"Wasted time is very high in the housing and building construction sector" and Koskela (2011) "suggests that 66% of on-site labour performs nonvalue activities and 10% of project materials are wasted" (Koskela, 2011;Zheng et al, 2017). "Decreasing waste accumulation on project construction sites leads to a competitive advantage in cost and schedule management" (Wang and Ma, 2013;Selkämaa, 2018).…”
Section: Reconciling the Lc Technology Paradigm With Budgeting Realitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…"Wasted time is very high in the housing and building construction sector" and Koskela (2011) "suggests that 66% of on-site labour performs nonvalue activities and 10% of project materials are wasted" (Koskela, 2011;Zheng et al, 2017). "Decreasing waste accumulation on project construction sites leads to a competitive advantage in cost and schedule management" (Wang and Ma, 2013;Selkämaa, 2018).…”
Section: Reconciling the Lc Technology Paradigm With Budgeting Realitiesmentioning
confidence: 99%
“…There are studies confirming that "average profits in the construction industry are 3% for contractors" (Sieng, 2012). According to Wang and Ma (2013) "an increase of 10% productivity in a construction/building firm in which labour (i.e. the payroll content/component) is 35% of total revenue will result in a doubling of the net profit, if the LC approach is correctly applied".…”
Section: Reconciling the Lc Technology Paradigm With Budgeting Realitiesmentioning
confidence: 99%
“…Several studies have shown that the most efficient production management methods are based on just-in-time philosophy [18,67,68]. Indeed, in a classical production scheme, the material flows from one station to another, passing through quite distinct stages; inspected and moved to the next post, or placed in stock waiting to resume its path.…”
Section: Comparative Summarymentioning
confidence: 99%